Reducing Elderly Poverty in Thailand : The Role of Thailand's Pension and Social Assistance Programs - World Bank (Washington, DC, 2017)
This policy note examines Thailand's programs for preventing poverty among the elderly, and suggests options for improving the effectiveness of these programs. The number of elderly people in Thailand will increase dramatically over the next 30 years, and the elderly already have a higher poverty rate than the population as a whole. Although Thailand currently has a total of eight pension programs, the majority of the benefits go to those who are not poor. In addition, unlike most countries, Thailand lacks a pension and provident fund supervision agency or a consolidated financial institution regulator, and does not appear to have a well-articulated national pension policy. This has led to the development of two major sets of pension programs, with one group sponsored by the ministry of labor and the social security office, and the other by the ministry of finance and the securities commission. These are also supplemented by an assortment of social assistance and community programs sponsored by the ministry of social development and human security and the ministry of interior. This policy note will examine the above issues in more detail and recommend policy options to simplify and coordinate the various pension and social assistance programs aimed at preventing poverty among the elderly, target more spending at the elderly poor, and assure long-term fiscal sustainability.